2018
DOI: 10.1038/s41598-018-33886-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponins may be irreversibly modified by glycation: novel potential mechanisms of cardiac performance modulation

Abstract: Dynamic movements of the cardiac troponin complex are an important component of the cardiac cycle. Whether cardiac troponins are subjected to irreversible advanced glycation end-product (AGE) modification is unknown. This study interrogated human and rat cardiac troponin-C, troponin-I and troponin-T to identify endogenous AGE modifications using mass spectrometry (LC-MS/MS). AGE modifications were detected on two amino acid residues of human troponin-C (Lys6, Lys39), thirteen troponin-I residues (Lys36, Lys50,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…While this is the first report of cTnT carbonylation, other post translational modifications, such as phosphorylation, methionine oxidation, and glycosylation have been previously reported for cardiac troponin T, I, and C subunits present in myocardial contractile machinery [49][50][51]. The irreversible oxidative carbonylation can act as an alternative mechanism by which the protein may be dissociated from its complex in the myocardium and subsequently released into the blood.…”
Section: Spot Idmentioning
confidence: 67%
“…While this is the first report of cTnT carbonylation, other post translational modifications, such as phosphorylation, methionine oxidation, and glycosylation have been previously reported for cardiac troponin T, I, and C subunits present in myocardial contractile machinery [49][50][51]. The irreversible oxidative carbonylation can act as an alternative mechanism by which the protein may be dissociated from its complex in the myocardium and subsequently released into the blood.…”
Section: Spot Idmentioning
confidence: 67%
“…The detailed fragmentation spectrum showing b and y ion identification confirms the site-specific acetylation of K132 on TnI. B. Schematic illustrating troponin I binding regions demonstrating the location of the common lysines (4: K107, K132, K178, K194) found to be acetylated in cTnI by proteomic screens in rat and guinea pig [10,12]. K132 is within a region that binds cTnC and in the actin binding region.…”
Section: Lc-ms/msmentioning
confidence: 78%
“…These changes influence both the calcium sensitivity of myofilament steadystate isometric force production as well relaxation kinetics [1,7]. While phosphorylation has been the most studied PTM of sarcomeric proteins, it has become evident that many different modifications occur normally and in disease, including acetylation, glycation, oxidation, citrullination, and succinylation [8][9][10][11][12]. These PTMs have the potential to impact sarcomeric protein interactions and thereby alter the properties of contraction and relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the fructose-specific transporter GLUT5 is expressed in cardiomyocytes and provided evidence that fructose availability can modulate cardiomyocyte excitation-contraction coupling in vitro 12 . Additionally, fructose can directly impact structure and function of proteins via post-translational modifications which are both irreversible (advanced glycation end-products) and reversible (O-GlcNAcylation) 4 , 13 . The detrimental actions of fructose have been most well described in the liver, where increased fructose has been linked to lipid accumulation, ATP depletion, and insulin resistance 14 .…”
Section: Introductionmentioning
confidence: 99%